Phytochemical screening, total phenolic content and antiradical activity of Asplenium africanum (Aspleniaceae) and fruit of Megaphrinium macrostachyum (Marantaceae) - Joseph Privat ONDOa, Louis-Clément OBAMEa, Timoléon ANDZI BARHÉa, Gontran NSI AKOUEa & b, Edouard NSI EMVOa and Jacques LEBIBIa (Journal of Applied Pharmaceutical Science, 2013)
Extracts from two plants consumed by Mandrillus sphinx Lékédi Park of Gabon, Megaphrinium macrostachyum (fruit) and Asplenium africanum, were screened for their phytochemical and total phenolics contents and their antiradical activity. Total phenolics were determined spectrophotometrically using the Folin-Ciocalteu reagent and expressed as gallic acid equivalent (GAE) and proanthocyanidin contents were expressed as apple procyanidins equivalent (APE). The antiradical activity was determined spectrophotometrically by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. From the results, alkaloids, triterpenoids, polyphenols, reducing sugars and cardiac glycosides were revealed to be present in the two plants. The phenol content varies from 122.83±0.01 to 341.16±0.01 mg GAE/100 g of extract. Proanthocyanidins have ranged between 4.33±0.02 and 55.16±0.03 mg APE/100 g of extract. While antiradical activity (IC50) ranged between 406.65±0.04 and 876.21±0.03 µg/ml of extract. Both the phenolics and DPPH results of extracts were found in good agreement and suggest that these plants are not only interesting sources for phenolic antioxidants but also potential sources of bioactive compounds.
Keywords: Megaphrinium macrostachyum, Asplenium afric